2021
DOI: 10.1039/d0na00867b
|View full text |Cite
|
Sign up to set email alerts
|

Response of G protein-coupled receptor CED-1 in germline to polystyrene nanoparticles inCaenorhabditis elegans

Abstract: The deposition of certain amount of nanopolystyrene (NPS) could be observed in gonad of Caenorhabditis elegans. However, we still know little about the response of germline to NPS exposure. In...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…However, the combined effects of microplastics and nanoplastics, especially at predicted environmental relevant concentration, on organisms remains unclear. Herein, locomotion behavior and brood size, as sensitive ecological indicators, could more effectively reflect the potential biotoxicity of environmental pollutants [ 43 , 44 ]. Firstly, we used sensitive endpoints (brood size and locomotion behavior) to examine the combinational effects between PS-50 and PS-500 in nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combined effects of microplastics and nanoplastics, especially at predicted environmental relevant concentration, on organisms remains unclear. Herein, locomotion behavior and brood size, as sensitive ecological indicators, could more effectively reflect the potential biotoxicity of environmental pollutants [ 43 , 44 ]. Firstly, we used sensitive endpoints (brood size and locomotion behavior) to examine the combinational effects between PS-50 and PS-500 in nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…ROS reflect levels of oxidative stress and are an important contributor to aging and disease [ 39 ]. ROS production in nematodes was measured using the 5′,6′-chloromethyl-2′,7′-dichlorodihydrofluorescein diacetate (CM-H 2 DCFDA) fluorescent probe method [ 40 ]. The exposed nematodes were collected after washing 3 times with K-medium, and then placed in NGM plates containing 1 mL of CM-H2DCFDA (50 µM), fed OP50 and incubated for 2 h in an incubator at 20 °C.…”
Section: Methodsmentioning
confidence: 99%
“…G protein-coupled receptors (GPCRs) constitute the largest family of transmembrane ™ receptors, playing a crucial role in various physiological processes [18]. Prior research has demonstrated the involvement of GPCRs in innate/adaptive immunity, environmental signal detection, and pathogen defense in the model nematode Caenorhabditis elegans [19][20][21]. The prefix "sr" designates over 1300 potential chemoreceptor genes identified in C. elegans, which belong to the receptor superfamilies Sra (Sra, Srb, Srab, Sre) and Str (Srh, Str, Sri, Srd, Srj, Srm, Srn), and Srg (Srx, Srt, Srg, Sru, Srv, Srxa) [22].…”
Section: Introductionmentioning
confidence: 99%